2013
DOI: 10.1152/ajplung.00194.2013
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of lung mononuclear phagocytes during pneumonia: contribution of chemokine receptors

Abstract: Bacterial pneumonia is a common and dangerous illness. Mononuclear phagocytes, which comprise monocyte, resident and recruited macrophage, and dendritic cell subsets, are critical to antimicrobial defenses, but the dynamics of their recruitment to the lungs in pneumonia is not established. We hypothesized that chemokine-mediated traffic of mononuclear phagocytes is important in defense against bacterial pneumonia. In a mouse model of Klebsiella pneumonia, circulating Ly6Chi and, to a lesser extent, Ly6Clo mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 67 publications
2
34
0
Order By: Relevance
“…Previous studies have shown that inflammatory monocytes are involved in controlling inflammation in gram-negative pneumonia and abdominal infections. 8,9,[38][39][40][41][42] A lower number of inflammatory monocytes has been associated with increased lesions in the lung and in the intestinal lamina propria. 8,9,38,41 Other studies have shown that the CX3CR1/ CX3CL1 axis is involved in the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that inflammatory monocytes are involved in controlling inflammation in gram-negative pneumonia and abdominal infections. 8,9,[38][39][40][41][42] A lower number of inflammatory monocytes has been associated with increased lesions in the lung and in the intestinal lamina propria. 8,9,38,41 Other studies have shown that the CX3CR1/ CX3CL1 axis is involved in the pathogenesis of sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Once neutrophils are present in infected tissues, they employ the numerous effector functions in their arsenal to combat K. pneumoniae infection. Studies using both human neutrophils and mouse models of K. pneumoniae infection have noted the neutrophilic use of a number of processes to contain K. pneumoniae (22,(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171). These processes include phagocytosis/opsonophagocytosis, the production of inflammatory cytokines, and the release of antimicrobial compounds and structures, such as reactive oxygen species, serine proteases (e.g., neutrophil elastase), lactoferrin, lipocalin-2, myeloperoxidase, and neutrophil extracellular traps (NETs), to contain the bacteria and mediate clearance (22,(155)(156)(157)(158)(159)(160)(161)(162)(163)(164)(165)(166)(167)(168)(169)(170)(171).…”
Section: K Pneumoniae and Host Immune Defensesmentioning
confidence: 99%
“…There they can become activated to produce tumor necrosis factor (TNF) and inducible nitric oxide synthase (iNOS) and contribute to microbicidal responses (21). Recently, a potential role for CCR2 ϩ monocytes in defense against Klebsiella pneumoniae was suggested by infection of CCR2 Ϫ/Ϫ mice with K. pneumoniae strain 43816 (22). Here, we have used the murine model of K. pneumoniae infection to investigate the relative contributions of neutrophils and CCR2 ϩ monocytes to pulmonary clearance and survival.…”
mentioning
confidence: 99%